Pengaruh Promosi dan Kualitas Produk terhadap Minat Beli : Survei pada Konsumen Dodol Sirsak Aslina Singaparna Kabupaten Tasikmalaya - Zenal Mustofa (CV. Ulil Albab Corp, 2022)
The purpose of this study is to determine the effect of promotion and product quality on the buying interest of MSMEs Dodol Sirsak Aslina Singaparna Tasikmalaya Regency. The research method used is a questionnaire method with a survey approach of 100 respondents who are consumers of Dodol Soursop Aslina. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that product promotion and quality have a significant effect both partially and simultaneously on the buying interest of MSME consumers dodol Sirsak Aslina Singaparna Tasikmalaya Regency.